Does the level of Altruism of university students create a difference in their views on gamete donation and surrogacy? - DEMİRCİ, NURDAN; POTUR, DİLEK (My University, 2022)
Purpose: In Turkey, whose population is predominantly Muslim and where gamete donation and surrogacy are not legal, few studies have so far been conducted to examine university students’ views on these practices. For this reason, it is crucial to determine whether the altruism levels of university students who are at reproductive age in Turkey create a difference in their views on gamete donation and the legalization of surrogacy. Materials and Methods: This is a descriptive cross-sectional study. It was conducted in a Turkish university. A personal information form and the Altruism Inventory were administered to the participating students. A total of 3,979 students participated in the study. Results: More than half of the participants stated that surrogacy and gamete donation must be legal in Turkey. The mean altruism scores of those who advocated the legality of gamete donation in Turkey were similar to the mean scores of those who did not (p>0.05). On the other hand, the mean altruism scores of those who advocated the legality of surrogacy in Turkey were higher than the mean scores of those who did not (p<0.05). Conclusion: Although people have the freedom to make their own decisions about reproduction, the characteristics of the community of which they are a member, their beliefs, educational background, gender, and sub-dimensions of the Altruism Inventory such as charitableness and sociality can influence their views.
Keywords: Sağlık Bilimleri; Hemşirelik; Kadın Hastalıkları ve Doğum Hemşireliği; Health Sciences; Nursing; Gynecology and Obstetrics Nursing; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Yoğun Bakım Hemşireliği; Tıbbi ve Cerrahi Hemşirelik; Farmakoloji (hemşirelik); Annelik ve Ebelik; Onkoloji (hemşirelik); Hemşirelik (çeşitli); İleri ve Uzman Hemşirelik; Asistan Hemşirelik; LPN ve LVN; Genel Hemşirelik; Acil Tıp Hemşireliği; Critical Care Nursing; Medical and Surgical Nursing; Pharmacology (nursing); Maternity and Midwifery; Oncology (nursing); Nursing (miscellaneous); Advanced and Specialized Nursing; Nurse Assisting; LPN and LVN; General Nursing; Emergency Nursing; Gamete; donation; surrogacy; altruism